The UNESCO Heritage of the Aeolian Islands (Italy) Tourism, Sustainable Development and Territorial Management - Mariaclaudia Cusumano; Marco Ingrassia (Fuori Luogo)
Tourism represents one of the fastest-growing socio-economic sectors of our time. The Aeolian Islands are positioned in a strategic area of the southern Tyrrhenian Sea in Italy. The Archipelago of the Aeolian islands consists in seven small villages, focal points of a landscape stratified over time. These are particularly fragile and vulnerable socio-ecological systems for which it is necessary to ensure Sustainable Tourism that allows for the conservation of biodiversity, the protection of the land, and the enjoyment of the Natural Heritage for future generations.The Archipelago, in the last seventy years, has become a particularly attractive area; at the beginning, it was the cinematography, and then the inscription of the UNESCO World Heritage List occurred in 2000 to increase the popularity of the islands.Tourism flow accelerates the anthropic pressure on the territory and, if exercised systematically and uncontrolled, may incur over-tourism, causing irreversible damage to natural and social systems.This contribution aims to investigate how UNESCO branding has impacted the Archipelago. This contribution is based on the hypothesis that UNESCO recognition has accelerated the global notoriety of the islands, contributing to anthropogenic pressure factors that threaten the balance of territorial and social systems.